NFC Based Smart Biosensor – An Introduction to Battery-less Enzymatic Amperometric Glucose Sensor Based on NFC Technology. (2017) - Matoschitz, C.; Lurf, R.; Meindl, M.; Beisteiner, M.; Bammer, M.
Abstract: Biosensors are widely used as analytical devices for determination of medically relevant parameters, e.g. glucose, lactate and histamine. The possibility of easily available and low-cost sensors is a central need in mobile diagnostics and personal health monitoring. Therefore, biosensors combined with near field communication (NFC) technology enable simple and smart sensor solutions for electrical and non-electrical parameter measurements.